Effects of air temperature, photoperiod, and soil moisture on leaf senescence and dormancy depth in four subtropical tree species - Fucheng Wang; Yiming Liu; Heikki Hänninen; Jinbin Zheng; Yu Zhao; Wenwen Chang; Jiasheng Wu; Rui Zhang (Forestry Research)
Climate warming has substantially delayed the autumn phenology of trees over recent decades. As the primary focus of previous studies on autumn phenology has been on temperate tree species, the environmental regulation of leaf senescence in subtropical trees under distinct climatic conditions remains poorly understood. To address this gap, using climate chambers, we experimentally examined the effects of air temperature, photoperiod, and soil moisture on leaf senescence and dormancy depth in seedlings of four subtropical tree species. Our results showed that low temperature served as the primary environmental cue driving leaf senescence in all four species, whereas photoperiod and soil moisture had no significant effect on senescence under low-temperature conditions. However, under high-temperature conditions, both drought and short photoperiod accelerated leaf senescence. This suggests that during warm autumns in subtropical regions when the typical senescence trigger (low temperature) is absent, drought and photoperiod are alternative cues to ensure senescence occurs before the onset of winter. Furthermore, we found that leaf senescence and dormancy induction were not closely linked processes. Overall, our experimental results reveal the dominant role of air temperature and its interactions with alternative cues (photoperiod and soil moisture) in regulating autumn leaf senescence in subtropical trees, which challenges the common assumption for a majority of temperate tree species that the primary driver of leaf senescence is short photoperiod. These findings provide valuable insights into the ways trees adapt to subtropical environments.